Influence of Ag-concentration on TiO2-supported catalysts for photocatalytic degradation of microplastics PA66 in marine - Xueqin Wang; Siow Hwa Teo; Mohd Razali Shamsuddin; Newati Wid (Elsevier, 2024)
Over the past few years, microplastics pollution in marine environments has become a global concern. In this study, a series of silver-doped titanium dioxide (Ag/TiO2) photocatalysts were prepared by the photo-assisted deposition method as an alternative approach for the rapid removal of microplastics particles from aqueous media, specifically polyamide 66 (PA66), the major type of microplastics in marine. The physicochemical and optical properties of photocatalysts were analyzed by Scanning Electron Microscopy (SEM), X-ray Energy Dispersion Spectrum (EDS), X-ray Diffraction (XRD), Photoluminescence Spectroscopy (PL), and Ultravioletvisible Diffuse Reflectance Spectroscopy (UV–vis DRS). The characterization results of the photocatalysts indicated that the appropriate loading of Ag on TiO2 significantly enhanced the optical properties of the catalysts. Specifically, 1.5 % Ag/TiO2 (AT1.5) exhibited the best light absorption performance and the lowest bandgap value, effectively suppressing the recombination of photogenerated electron-hole pairs. Furthermore, a series of photocatalytic degradation experiments confirmed that AT1.5 exhibited optimal performance in degrading PA66. Under UVA irradiation for 4 hours, the photocatalytic degradation of PA66 by AT1.5 resulted in a mass loss of 58.9 %. The degradation rate of PA66 increased with the amount of catalyst. When the mass ratio of AT1.5 to PA66 was 3:1, PA66 experienced 100 % mass loss after 4 hours of UVA exposure. Finally, through qualitative analysis, this study proposed the possible pathways and mechanisms for the photocatalytic degradation of PA66 by Ag/TiO2. Despite the challenges posed by microplastics pollution to marine ecosystems, this research provides a rapid and effective degradation method.